Women in the Private and Public Life: the Iconic Statuesque of Aquileia (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
At a first examination, is impossible not to notice that the statue-portrait of women in Aquileia form a rather narrow group and not yet studied as a whole, although the material has long been known. We therefore intend to resume the analysis to verify since when the use of this form of representation for women is certified. We also want to study the duration, its function, private or public, the reference models, and its value in the figurative production of Aquileia.
Keywords: Aquileia; sculpture; women; female statuary tipes; greek models; workshops